The Role of Governance, GDP, and Inflation in Attracting Foreign Investment: Empirical Evidence in ASEAN - Kuswara, Arif Rahman; Pratama, Bima Cinintya; Purwidianti, Wida; Kusbandiyah, Ani (E-Jurnal Akuntansi, 2025)
This study aims to examine the factors of governmental and non-governmental governance that influence FDI in ASEAN countries, with a research sample from 2005 to 2023. The factors of governmental governance are represented by the rule of law, government effectiveness, and regulatory quality. This study uses quantitative research. Quantitative data was obtained using secondary data in the form of Governance Data documentation from the Worldwide Governance Indicators (WGI) from the World Bank. FDI Data is in the form of FDI flow data from World Development Indicators (WDI), UNCTAD, and national investment agencies (BKPM for Indonesia). The analysis method used is multiple linear regression using STATA17. The results of the study show that regulatory quality and inflation have a positive effect on FDI. Meanwhile, the factors of rule of law, government effectiveness, and GDP have no effect on FDI. The contribution of this study is to serve as a practical guide for the government and policymakers in designing strategic programs for the quality of government regulations and inflation stability policies in order to attract FDI to Indonesia.